Practical Paint.NET : the powerful no-cost image editor for Microsoft Windows - Whitt, Phillip (Digital image editor) (Apress, 2022)
Learn to use the most up-to-date version of Paint.NET, the free, Windows-based program for image editing. This book is ideal for PC users who find Microsoft Paint too lacking, and Photoshop or GIMP too overwhelming. Paint.NET is a lightweight yet capable program thats easy to navigate and is regularly updated. Youll quickly become acquainted with this powerful, yet easy-to-learn programs features; tools, layers, adjustments, and effects. See how to correct exposure, digitally retouch and repair damaged photos, and handle a broad spectrum of photo editing taskseven how to colorize a black-and-white image. Youll also learn how to create digital art using the Paint.NET drawing tools and effects. Practice files are provided with step-by-step instructions to jump into photo editing and art creation. Practical Paint.NET highlights this powerful program's rich set of features and capabilities providing you the pathway for just about any kind of image editing. Join the large community behind it today! You will: Use layers, which are essential in any professional quality image editing program Acquire and install plugins to maximize Paint.NETs capabilities Enhance, retouch, and modify digital images Create compelling digital artwork using the drawing tools and applying artistic filters.